Sorting based on amenities and income composition: Evidence on the multiplier effect - Mark van Duijn; Jan Rouwendal (European Regional Science Association (ERSA), 2013)
Recent research shows that urban heritage can be an important factor of residential location choice, and that especially highly educated households are attracted by the presence of cultural heritage. In this paper, we use a location choice model to investigate the attractiveness of neighborhood amenities for homeowners with a higher income in Amsterdam and surrounding municipalities. We control for observed (house prices, proximity to large labor markets, area of historic city center, share of rich households) and unobserved neighborhood characteristics. Since the attractiveness of neighborhoods may be affected by amenities of surrounding neighborhoods, we extend the model by incorporating these spillover effects. We use a unique data set where we identify the marginal willingness-to-pay of these different households for living within or near the historic city center. The results show that high income households not only prefer to live close to each other, but also prefer to live close to the historic city center. Also the number of shops seem to be higher in the historic city center. This suggests that there are multiplier effects regarding the effect of historic city centers.
Keywords: 330; cultural heritage; income composition; multiplier effect; equilibrium sorting models; discrete choice models; unobserved characteristics; heterogeneous household preferences